Some critical issues in tests taken from CELI and CILS certifications (Italian as a Foreign Language) - Torresan, Paolo (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2016)
This paper aims to sum up 3 years of research into the CELI and CILS certifications in Italian as a Foreign Language, the results of which have been reported in several articles and essays. We have discovered some sources of bias affecting the quality of the exams. Here, these areas of bias are briefly described and classified into groups.